Four dimensions to observe a Triple Helix: invention of `cored model' and differentiation of institutional and functional spheres - Chunyan Zhou (Triple Helix, 2014)
This investigation utilizes a matrix observation method to analyze triple helices. Firstly, by analyzing a unique Chinese academic phenomenon, the university-run enterprise (URE), a 'cored model' is proposed to complement the existing non-cored model of a triple helix study. The URE remains within the university administration, in contrast to the US spin-off firm that exits quickly. This difference raises the issue of how boundaries among the institutional spheres should be defined. Secondly, institutional and functional spheres are differentiated as separate concepts. Based on the theoretical research, a matrix observation method of a triple helix is invented. Finally, as a typical case, we observe Chinese triple helix (CTH), showing how to use the observation method. The most important contribution of this research is that it develops a methodology to analyze a triple helix through a matrix with four dimensions (Table one). Two questions have been explored and they are as follows: (1) Should a URE remain within university administration? (2) How may the Chinese triple helix with a dominant government role be improved?
Keywords: 330; Chinese triple helix (CTH); Functional sphere; Institutional sphere; Triple helix cored model; University-run enterprises (UREs)